Pencegahan Kecurangan Dalam Pengelolaan Dana Desa - Made Resmiani; I Putu Gede Diatmika (Jurnal Akuntansi Profesi, 2022)
The government, in this case the village government is under the spotlight of various parties regarding their functions and duties to manage public funds where fraud is vulnerable. This study aims to determine: (1) the influence of organizational culture on fraud prevention in village fund management, (2) the effect of human resource competence on fraud prevention in village fund management, (3) the effect of the effectiveness of internal control on fraud prevention in village fund management. The type of approach used is a quantitative approach. The population used in this study were all village officials as many as 153 people. While the determination of the sample with purposive sampling technique so that the sample obtained as many as 82 village / respondent. Data collection using a questionnaire distributed directly to the field with due regard to health protocols.The results of the research conducted are: (1) organizational culture has a significant positive effect on fraud prevention in village fund management, (2) human resource competence has a significant positive effect on fraud prevention in village fund management, (3) the effectiveness of internal control has a significant positive effect on preventing fraud in managing village funds. This research is expected to improve organizational culture, human resource competency, and effectiveness of internal control so as to avoid various forms of fraud in the management of village funds.